The Role of Neoantigens in Cancer Immunotherapy - Zhu, Yueting; Liu, Jiyan (Frontiers in Oncology, 2021)
Somatic mutation-derived neoantigens, expressed only on tumor cells, may elicit antitumor T-cell responses in cancer immunotherapies with minimal immune tolerance. Neoantigens can be identified by multiple bioinformatics technologies, mainly based on whole-exome sequencing. Personalized cancer vaccines and adoptive T cell therapies are two main treatment modalities targeting neoantigens, and both of them have shown promising therapeutic effects. In this review, we summarize the history of neoantigen-related tumor control, introduce recent methods in neoantigen screening and identification, and discuss the role of neoantigen in cancer immunotherapies. Moreover, we propose the challenges of targeting neoantigens for cancer treatment.